Development of A Web Based Chronic Drug Claims Management Information System Using the Fast (Framework for the Applications of Systems Thingking) Methodology - Rr. Devi Noviana Setyoningsih; Cahya Tri Purnami; Antono Suryoputro Yudhy Dharmawan; Aris Puji Widodo (GLOBAL HEALTH SCIENCE GROUP, 2025)
Delays of chronic drug claims caused delayed payments to the next period. The impact was disrupting the hospital's cash flow, delaying employee incentives, and creating difficulty in providing chronic drugs needed by patients. To address these operational challenges, RSUD Kajen seeks to implement a computerized drug claims information. This system will streamline processes, resolve existing inefficiencies, and improve overall patient care delivery while ensuring timely claims submission. The implementation of a computerized drug claims information system successfully facilitates claims management and improves services at RSUD Kajen.